LITERARY CRITICISM IN THE DIGITAL AGE: ADDRESSING THE PROBLEMS AND OPPORTUNITIES OF DIGITAL LITERATURE IN EFL PEDAGOGY - Ali Mustofa; Lies Amin Lestari (English Review: Journal of English Education, 2023)
The literary genre known as "digital literature" includes works of fiction and nonfiction written only for digital media such as computers, tablets, and smartphones. Because of its convenient qualities, this genre may be read and enjoyed anywhere, especially when it has already been posted to a digital site. Such literary works might not offer universal traits like those of works on paper. This is just unusual in that it is solely made with digital tools. Digital literature may provide particular techniques to reading and analyzing it, since the academic world likewise moves toward paperless resources. The current study examines the difficulties, limitations, and potential solutions for seeing digital literary works as online resources, using some novel methods from literary and cultural studies and multimodality that may be used to evaluate digital literary texts. The article presents and examines a few ideas that will significantly improve the actions and reactions of EFL students’ active participation in literary criticism and analysis